Legal perspective of female circumcision: study of woman rights to access information of sexual health in Indonesian knowledge (Research, Society and Development, 2020)
Female circumcision is a controversial practice in some countries, including Indonesia. This study aims to know the implication of female circumcision in Indonesia, especially in Situbondo, Surabaya and Bangkalan. Quantitative methodology is used as the methodology, while the samples are taken through random sampling and given questionnaire and interview. The finding showed that most women are still does not know about the function of female circumcision, they only following the tradition within their community. The patriarchy culture that view woman as a lower creature makes woman cannot get her right in asking about reproductive health. It even considered as taboo and unnecessary. Female circumcision that firstly legalized by the Health Minister is now prohibited due to health problem. Therefore, female circumcision is no longer legal in Indonesia.